2001
DOI: 10.1097/00006676-200103000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Neural Cell Adhesion Molecule in Pancreatic Cancer

Abstract: Neural cell adhesion molecule (NCAM) has been found to be a significant factor for survival in various solid tumors. In the present study, we examined the expression of NCAM in exocrine tumors of the pancreas by immunohistochemistry, using two monoclonal antibodies against NCAM and polysialic acid (MAB735). Expression of NCAM was seen mainly in the cytoplasm of the following cells: regenerating duct cells among neoplastic tissue, hyperplastic islet cells, intrapancreatic nerves and ganglia, as well as tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…The therapeutic use of anti-NCAM antibodies will be limited, however, by the possibility that metastasis formation may be enhanced through NCAM blocking. NCAM expression tends to be lost in metastatic lesions [18][19][20]23 and, conversely, aberrant expression of L1-CAM in carcinomas was reported to enhance tumor growth and cell migration. According to the herein reported findings, both conditions would augment tumor cell recognition by NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic use of anti-NCAM antibodies will be limited, however, by the possibility that metastasis formation may be enhanced through NCAM blocking. NCAM expression tends to be lost in metastatic lesions [18][19][20]23 and, conversely, aberrant expression of L1-CAM in carcinomas was reported to enhance tumor growth and cell migration. According to the herein reported findings, both conditions would augment tumor cell recognition by NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…13 NCAM expression is a marker for neuroendocrine carcinomas of the lung 14,15 and in other organs. 16,17 Aberrant expression has also been detected in renal cell carcinoma, 18 pancreatic adenocarcinoma and b cell tumors, 19,20 in tumors of the salivary gland 21 and gall bladder, 22 and cases of breast and colon carcinoma. 23,24 In line with the adhesive functions of NCAM, low or absent NCAM expression in carcinomas was correlated with a metastatic phenotype and poor survival rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diminished expression of NCAM was also associated with clinically aggressive colon cancers (Sampson-Johannes et al, 1996;Roesler et al, 1997;Huerta et al, 2001), and dissemination of pancreatic b-tumour cells (Perl et al, 1999;Cavallaro et al, 2001). Tezel et al (2001) suggested that NCAM expression in tubular adenocarcinoma of the pancreas has a significant impact on overall patient survival. We recently demonstrated an inverse correlation between NCAM expression and NB cell adhesion, assessed on 11 NB cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…NCAM has been shown to play an important role in the progression to tumor malignancy. Both the shift of the adult NCAM 120-kDa isoform to the embryonic 140-and 180-kDa isoforms and a general downregulation of NCAM expression are associated with poor prognosis in a few cancer types [50,51]. In a transgenic mouse tumor model of pancreatic b cell carcinogenesis (Rip1Tag2), loss of NCAM leads to the formation of lymph node metastasis mediated by the increased expression of the lymphangiogenic factors VEGF-C and D and with it upregulated peri-tumoral lymphangiogenesis [52,53].…”
Section: Integrins and Tumor Progressionmentioning
confidence: 99%